PERLINDUNGAN HUKUM BAGI APARATUR NEGARA DALAM PENYELESAIAN SENGKETA KEPEGAWAIAN PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Harahap, Nurmalita Ayuningtyas (Jurnal Yuridis, 2016)
Changes in regulations concerning employment, in particular regarding dispute resolution mechanisms State Civil Apparatus then indirectly affect the implementation of dispute resolution for the State Civil Apparatus. In contrast to what was in the previous law that the administrative appeals filed with the Personnel Advisory Board. In Article 129 of Constitution Number  5 of 2014 about civilian state apparatus.arranged among others on the administrative appeal submitted to the Advisory Board of civilian state apparatus, in which the efforts of administrative appeals and on the Advisory Board of the civilian state apparatus regulated by Government Regulation. But until now the government regulation has not been issued so that the dispute settlement civilian state apparatus, particularly for government employees with work agreementwill be problems in implementation.Legal protection of the state apparatus in the employment dispute resolution after the enactment of Constitution Number  5 of 2014 about civilian state apparatus  can not be optimal be given and legal protection that the government can do isimmediately issued Government Regulation.